The Existence of Insects and Their Role on Rice (Oryza sativa L.) Agriculture in Medang Village, Batu Bara District, North Sumatra - Hafizah Asby; Masitta Tanjung; Suci Rahayu (Jurnal Penelitian Pendidikan IPA, 2025)
Research on insect diversity on rice (Oryza sativa L.) agricultural land in Medang Lama Village, Medang Deras District, Batu Bara Regency was carried out in June-December 2024.The research aims to analyze insect species and the role of insects at different growth periods, namely the vegetative period (25-30), the generative period (55-50), and the maturation period (85-90) days after planting (DAP), The method for determining sampling points is carried out using the Purposive Sampling method, while sampling uses the Insecting Net, Visual Control, Hand Sorting and Light Trap methods. The research results showed that the insects obtained were 31 species, 24 families and 7 orders. The highest number of insects was found during the generative period, 173 individuals, 81 individuals during the vegetative period, and the lowest during the maturation period, 56 individuals. During the vegetative period, 10 pest species, 5 predator species and 1 pollinator species were found. During the generative period, 13 pest species, 10 predator species and 6 pollinator species were found. During the ripening period, 6 pest species, 5 predator species and 3 pollinator species were found. Pest insects are predominantly from the Hemiptera order, predatory insects are predominantly from the Coloptera order and pollinator insects are predominantly from the Hymenoptera order. Insect pests attack more often during the vegetative and generative periods than during the ripening period of rice plants.